2003
DOI: 10.1097/01.wcb.0000088763.02615.79
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Analysis of Hippocampal Gene Expression Measured Twelve Hours after Hypoxia-Ischemia in the Mouse

Abstract: Summary:Cell death from cerebral ischemia is a dynamic process. In the minutes to days after an ischemic insult, progressive changes in cellular morphology occur. Associated with these events is the regulation of competing programs of gene expression; some are protective against ischemic insult, and others contribute to delayed cell death. Many genes involved in these processes have been identified, but individually, these findings have provided only limited insight into the systems biology of cerebral ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Today, cDNA microarray technology provides a powerful tool for investigating parallel expression changes for thousands of genes at one time. Several microarray approaches have been tried in different hypoxic systems, including hypoxic lung, endothelial cells, fibroblasts, breast cancer cells (MCF-7 and MDA-MB-231), cerebral cortical neurons, hippocampus, and zebrafish exposed to hypoxia (8)(9)(10). However, to the best of our knowledge, the gene expression profile of hypoxia preconditioning in heart has not been identified.…”
Section: Introductionmentioning
confidence: 93%
“…Today, cDNA microarray technology provides a powerful tool for investigating parallel expression changes for thousands of genes at one time. Several microarray approaches have been tried in different hypoxic systems, including hypoxic lung, endothelial cells, fibroblasts, breast cancer cells (MCF-7 and MDA-MB-231), cerebral cortical neurons, hippocampus, and zebrafish exposed to hypoxia (8)(9)(10). However, to the best of our knowledge, the gene expression profile of hypoxia preconditioning in heart has not been identified.…”
Section: Introductionmentioning
confidence: 93%
“…Microarray studies investigating the transcriptome of both focal and global ischemia showed that the differentially expressed genes involved immediate early genes, stress response genes, apoptosis, signal transduction, neurotransmission, ion channels, inflammation, cytoskeleton, ribosome, and neurotrophic factors, et al (Buttner et al 2009; Cox-Limpens et al 2014; Gilbert et al 2003; Hori et al 2012; Jin et al 2001b; Lu et al 2003; Lu et al 2004; Ramos-Cejudo et al 2012; Sarabi et al 2008; Schmidt-Kastner et al 2002; Soriano et al 2000; Sun et al 2007; Tang et al 2002; Wang et al 2011a; Yakubov et al 2004). …”
Section: Endogenous Protective Mechanisms and Secreted Help-me Sigmentioning
confidence: 99%
“…Several previous studies that have investigated changes in gene expression after adult ischemia have focused on the cortex (Kim et al, 2002;Lu et al, 2003;Schmidt-Kastner et al, 2002) or hippocampus (Gilbert et al, 2003;Jin et al, 2001) only. Because the injury after neonatal HI develops in other regions as well, choosing only one specific region would potentially leave out important genes that are expressed locally in distinct areas.…”
Section: Discussionmentioning
confidence: 99%